DOMAIN NAME DISPUTE RESOLUTION IN INDIA: A MANIFESTATION OF THE ARBITRATION REGIME & PRIVACY ISSUES - et. al., Shirish Kulkarni (International Journal of Modern Agriculture, 2021)
The Domain Name Regulation in India is a wide umbrella of laws, regulations and policies that are both statutory and sub-delegated in nature. While domain names do usually come under the perspective of the Trademark Act, 1999, there is considerable legitimacy in the Domain Name Dispute Resolution Process provided under UDRP i.e. Uniform Dispute Resolution Policy and the WIPO being the Dispute Settlement Body and INDRP under the .IN Registry Dispute Resolution Policy with insights from UNDRP and the IT Act, 2000. While UDRP and INDRP appear as methods involving Alternative Dispute Resolution with the exception of a mandate to submit to arbitration, the common law remedy of Passing Off is still valid and used for domain name disputes. In this paper, it is attempted to observe and inquire into the intersection of remedies available under INDRP/UDRP, Arbitral Proceedings and the Common Law Remedy. Indian Judicial Approach towards Trademarks has been rather consistent in terms of bringing Domain Name Disputes under the ambit of Common Law..